Apolipoprotein e and Paraoxonase 1 polymorphisms are associated with lower serum thyroid hormones in postmenopausal women - Lambrinoudaki, I.; Kaparos, G.; Rizos, D.; Galapi, F.; Alexandrou, A; Sergentanis, T.N.; Creatsa, M.; Christodoulakos, G.; Kouskouni, E.; Botsis, D. (Clinical Endocrinology, 2009)
Objective Autoimmune thyroiditis and overt or subclinical hypothyroidism have been associated with increased prevalence of cardiovascular disease (CVD). Design Cross-sectional investigation of the association between gene polymorphisms related to CVD with thyroid function and autoimmunity. Patients In total 84 healthy postmenopausal women aged 49-69 years. Measurements FT3, FT4, anti-TPO and anti-TG were assessed in the sera of participants. The following polymorphisms were assessed from peripheral lymphocyte DNA: Apolipoprotein E E2/E3/E4, paraoxonase 1 A/B, Glycoprotein IIIa leu33pro, MTHFR ala222val, ApoBarg3500gln, plasminogen activator inhibitor 1 4G/5G, cholesterol 7-α hydroxylase A204C and cholesterol ester transfer protein B1/B2. Results A statistically significant correlation was found between Apolipoprotein E and paraoxonase1 polymorphisms and serum thyroid hormones: carriers of the E2 or E4 allele of the ApoE gene had lower levels of FT4 (P = 0·0005) than women with the E3/E3 genotype. Carriers of the B allele of paraoxonase 1 gene had lower levels of FT3 compared to women with the wild-type genotype (P = 0·047). A statistically significant positive association (P = 0·049) was also observed between anti-TG antibodies and the presence of the E2 allele of the Apolipoprotein E gene. Conclusions Polymorphisms of apolipoprotein E and paraoxonase 1 are associated with different levels of thyroid hormone and anti-Tg antibody levels in the study population in this pilot study. The mechanism underlying this association remains to be elucidated. © 2009 Blackwell Publishing Ltd.